A Case of Immun Thrombocytopenic Purpura Relapsed During Lithium Administration - Kurtoğlu, Erdal; Tunç, Ahmet; Uğur, Ayşegül (Fırat University, 2003)
Aim: Immun thrombocytopenic purpura (ITP) is a disease characterized by early destruction of platelets by antibodies attached onto platelet surface. Mechanisms responsible for this destruction have not been clarified yet. But some infectious agents, some drugs, and their metabolites are claimed to be responsible. Case: Twenty-four years old female was diagnosed as ITP and was successfully treated by oral steroid. After 16 months she was admitted to hospital because she had fatigue and her platelet count was 16x109/L. It was learned that she used lithium for manic-depressive episode. Following the withdrawal of the drug her plateler count recovered. Conclusion: It is well known that some drugs and their metabolites are responsible for ITP. Use of such drugs or any other drug should be used carefully, and in the case of any suspicion their use should be limited or prohibited in ITP patients.

Amaç: İmmün trombositopenik purpura (İTP), trombositlerin yüzeyine yapışan antikorların erken trombosit yıkımına neden olması ile karakterize bir hastalıktır. Bu yıkıma neden olan mekanizmalar henüz tam olarak aydınlatılamamıştır. Fakat bazı infeksiyöz ajanlar ve ilaçlarla onların metabolitleri bu nedenle suçlanmaktadırlar. Olgu: 24 yaşındaki bayan hastaya İTP tanısı konuldu ve steroid ile başarı ile tedavi edildi. 16 ay sonra hasta, halsizlik yakınması ile tekrar kliniğimize başvurdu ve trombosit sayısı 16x109/L bulundu. Hastamızın manik-depresif bozukluk nedeni ile lityum kullandığı öğrenildi. İlacın kullanımına son verildikten sonra trombosit sayısı normale döndü. Sonuç: Bazı ilaçların ve onların metabolitlerinin İTP'ya neden oldukları çok iyi bilinmektedir. İTP hastalarında, bu tür ilaçların veya herhangi bir ilacın kullanımında çok dikkatli davranılmalı, herhangi bir şüphe anında ilaç kullanımı kısıtlanmalı veya tümüyle engellenmelidir.
Lityum Kullanımı Sırasında Nüks Eden Bir İmmün Trombositopenik Purpura Olgusu